Perubahan pada Lingkungan Kerja selama Pandemi : Dampaknya terhadap Produktivitas Karyawan - I Gusti Ngurah Widya Hadi Saputra; Haevita Astriena Natalia (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
Changes in the work environment due to the Covid-19 pandemic are being felt in almost all over the world, including in Indonesia. The policy taken by the government to reduce the spread of the pandemic through physical distancing and work from home requires employees to change the way they work. The purpose of this study was to determine the effect of work from home and its impact on employee productivity in Bali. The sample used was 100 respondents. The method used is a quantitative method using partial least square (PLS) and analyzed using the SmartPLS program. Based on the processed data, the result shows that work from home and non-physical work environment have a significant effect on employee productivity. Meanwhile, work from home policies and changes in the work environment to non-physical through technostress have no effect on employee productivity.